Predictors of pre-rehabilitation exercise capacity in elderly European cardiac patients – The EU-CaRE study. (November 2020) - Marcin, Thimo; Eser, Prisca; Prescott, Eva; Mikkelsen, Nicolai; Prins, Leonie F; Kolkman, Evelien K; Lado-Baleato, Óscar; Cardaso-Suaréz, Carmen; Bruins, Wendy; van der Velde, Astrid E; Peña Gil, Carlos; Iliou, Marie Christine; et al.
Aims: Functional capacity is an important endpoint for therapies oriented to older adults with cardiovascular diseases. The literature on predictors of exercise capacity is sparse in the elderly population. In a longitudinal European study on effectiveness of cardiac rehabilitation of seven European countries in elderly (>65 years) coronary artery disease or valvular heart disease patients, predictors for baseline exercise capacity were determined, and reference ranges for elderly cardiac patients provided. Methods: Mixed models were performed in 1282 patients (mean age 72.9 ± 5.4 years, 79% male) for peak oxygen consumption relative to weight (peak VO2 ; ml/kg per min) with centre as random factor and patient anthropometric, demographic, social, psychological and nutritional parameters, as well as disease aetiology, procedure, comorbidities and cardiovascular risk factors as fixed factors. Results: The most important predictors for low peak VO2 were coronary artery bypass grafting or valve surgery, low resting forced expiratory volume, reduced left ventricular ejection fraction, nephropathy and peripheral arterial disease. Each cumulative comorbidity or cardiovascular risk factors reduced exercise capacity by 1.7 ml/kg per min and 1.1 ml/kg per min, respectively. Males had a higher peak VO2 per body mass but not per lean mass. Haemoglobin was significantly linked to peak VO2 in both surgery and non-surgery patients. Conclusions: Surgical procedures, cumulative comorbidities and cardiovascular risk factors were the factors with the strongest relation to reduced exercise capacity in the elderly. Expression of peak VO2 per lean mass rather than body mass allows a more appropriate comparison between sexes. Haemoglobin is strongly related to peak VO2 and should be considered in studies assessing exercise capacity, especially in studies on patients after cardiac surgery.